STRATEGIC MANAGEMENT OF INQUIRY-BASED MULTIPLE INTELLIGENCES FOR ENHANCING PAI LEARNING ACHIEVEMENT - Syaifullah; Amirkhan, Ozi Ali (Universitas Nurul Jadid, 2023)
This study explores the effectiveness of inquiry-based MI learning in improving students' understanding of PAI concepts, increasing student involvement in the learning process, and evaluating measurable increases in learning achievement in PAI subjects. This study aimed to investigate and evaluate the effectiveness of Inquiry-Based Multiple Intelligences (MI) Implementation in improving student achievement in Islamic Religious Education (PAI) subjects at SMP Nurul Jadid Paiton Probolinggo. In designing this research, researchers used a qualitative approach and a type of case study. Researchers collect research data using three research techniques: in-depth interviews, participant observation, and documentation studies. Researchers used participant observation methods. This study used qualitative descriptive analysis of Miles and Huberman types. This study aimed to investigate and evaluate the effectiveness of Inquiry-Based Multiple Intelligences (MI) Implementation in improving student achievement in Islamic Religious Education (PAI) subjects at SMP Nurul Jadid Paiton Probolinggo. The results showed that implementing the Islamic Religious Learning (PAI) strategy with the Inquiry-Based Multiple Intelligences (MI) Implementation approach at SMP Nurul Jadid Paiton Probolinggo significantly impacted the learning process and student achievement. This approach increases student participation and facilitates their involvement in the learning process.